Closing the Door on Survivors: How anti-trafficking programmes in the US limit access to housing - Romero, Karen; Torres, Tatiana; Jones, Alana; Dacosta-Reyes, Ciara (Anti-Trafficking Review, 2023)
Housing is often an immediate need for survivors as they exit a trafficking situation. Due to financial hardship, housing availability, and other barriers, many survivors rely on time-limited housing options, some which are offered by anti-trafficking service providers. As such, the anti-trafficking field has begun to adopt trauma-informed approaches to housing to meet the needs of survivors. In this paper, we present an analysis of policies and procedures from 73 US anti-trafficking housing programmes on the implementation of a trauma-informed model. We argue that mandatory requirements limit the implementation of trauma-informed service delivery. Additionally, practices such as the voluntary services model can be leveraged to increase trauma-informed approaches in housing services. Lessons learnt from this process can inform the revision of punitive policies and procedures in favour of those that are voluntary and trauma-informed.